2021
DOI: 10.1016/j.janxdis.2021.102415
|View full text |Cite
|
Sign up to set email alerts
|

The latent and item structure of COVID-19 fear: A comparison of four COVID-19 fear questionnaires using SEM and network analyses

Abstract: Since the outbreak of the coronavirus disease (COVID-19), several reports have shown that fear relating to COVID-19 has sharply increased. To measure fear of COVID-19, various questionnaires have been developed in parallel. However, fear concerning COVID-19 is not necessarily a uniform construct and the different questionnaires may cover diverse aspects. To examine the underlying structure of fear of COVID-19, we conducted structural equation modelling and network analyses on four scales in an online convenien… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(65 citation statements)
references
References 43 publications
4
57
0
4
Order By: Relevance
“…Positive correlations between the FCV-19S and CSS have been also demonstrated in other studies aiming at developing non-English versions of the CSS-PL (e.g., the Persian and Arabic versions of the CCS [ 11 , 44 ]. This pattern of associations between the CSS and FCV-19S also suggest that the FCV-19S appears to capture two constructs measured by the CSS, i.e., the danger and contamination and the traumatic symptoms and checking constructs [ 48 ]. The CSS-PL scales also demonstrated moderate to large associations with measures of anxiety-related traits and obsessive-compulsive symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Positive correlations between the FCV-19S and CSS have been also demonstrated in other studies aiming at developing non-English versions of the CSS-PL (e.g., the Persian and Arabic versions of the CCS [ 11 , 44 ]. This pattern of associations between the CSS and FCV-19S also suggest that the FCV-19S appears to capture two constructs measured by the CSS, i.e., the danger and contamination and the traumatic symptoms and checking constructs [ 48 ]. The CSS-PL scales also demonstrated moderate to large associations with measures of anxiety-related traits and obsessive-compulsive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, although our investigation included participants across a wide age range (from 18 to 85 years), participants 60 years and older represented only 17.30% of the total sample ( n = 96). This age group is particularly salient given the mortality rates of COVID-19, and potentially more COVID-19 fear, among older individuals [ 48 ]. Further, our sample was over 60% female, and there is evidence for gender differences in regard to attitudes and behaviors towards COVID-19 (e.g., women were more likely to perceive COVID-19 as a very serious health problem and support/comply with restrictive public policies in response to COVID-19 [ 49 ].…”
Section: Limitationsmentioning
confidence: 99%
“…Similarly, Ralph [42] considered fear as an intervening variable between sets of context-dependent stimuli and suites of behavioral responses. A wide range of threats can elicit fear, and given that COVID-19 is affecting our lives in many ways (e.g., on a social, economic, relational, and professional level), fears elicited by COVID-19 may be considerably heterogeneous [43]. Fear can be beneficial or detrimental to mental and physical health during the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Another limitation is that fear of COVID-19 was only measured with one specific scale (i.e., the FCQ developed by . However, prior research has found that fear of COVID-19 is a multifaceted construct that also includes concerns about the socio-economic consequences of COVID, xenophobia, and stress-related symptoms (e.g., nightmares) (Mertens et al, 2021;Taylor et al, 2020). It is possible that these other facets of fear of COVID-19 are FEAR PREDICTS VACCINATION WILLINGNESS 22 also related to vaccination willingness.…”
Section: Discussionmentioning
confidence: 99%